KAJIAN DAMPAK LINGKUNGAN PRODUK TEPUNG AGAR MENGGUNAKAN METODE LIFE CYCLE ASSESSMENT (LCA) - Siti Aminatu Zuhria; Nastiti Siswi Indrasti; Mohamad Yani (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Gracilaria sp is one type of red algae seaweed that has been developed in Indonesia. Gracilaria sp isused as raw material for agar flour. Currently, agar flour is widely used to meet the needs of both food and nonfood industries. Therefore, agar flour must be developed to obtain the best quality, adequate quantity, and ecofriendly. This study aimed to identify the inputs, outputs, and environmental impacts of the agar flour product'slife cycle, determine the source of the impact (hotspot), and recommend improvement scenarios. The method usedto analyze the environmental impact caused by a product was life cycle assessment (LCA). The scope of the LCAstudy was cradle to gate, namely cultivation of Gracilaria sp, transportation of raw material to industry, andproduction process in the industry. The environmental impact study was global warming with CO2eq unit,acidification with SO2eq unit, and eutrophication with PO4eq unit. Based on the research, the impacts of globalwarming, acidification, and eutrophication on the life cycle of agar flour were 26.28 kg-CO2eq/kg agar flour, 0.18kg-SO2eq/kg agar flour, and 0.03 kg-PO4eq/kg, respectively. The production process unit was hotspot for theimpact of global warming, acidification, and eutrophication on the life cycle of agar flour. The improvementscenarios to reduce the environmental impacts included replacing urea with NPK fertilizer, finding suppliers ofraw materials closer to the industry, and replacing coal with Compressed Natural Gas (CNG). Keywords: agar flour, environmental impact, global warming, life cycle assessment